2019
DOI: 10.1111/ijpo.12588
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational associations of dietary inflammatory index with birth outcomes and weight status at age 5 and 9: Results from the Lifeways cross‐generation cohort study

Abstract: Summary Background Maternal diet and chronic inflammation may influence early‐life offspring health. No comparative data regarding intergenerational associations between dietary inflammation and offspring growth exist. Objective To investigate potential associations between parental and grandparental dietary inflammatory index (DII®) scores with offspring birth outcomes and childhood adiposity. Methods This analysis of the Lifeways Study includes 1082 mother‐child pairs, 333 index‐child's fathers and 707 grand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
(99 reference statements)
0
16
0
2
Order By: Relevance
“…In a variety of pregnancy cohorts, the DII ® or E-DII TM has been associated with outcomes such as maternal inflammation, gestational diabetes mellitus (GDM), preterm birth, birthweight, and neonatal adiposity, particularly in women with overweight and obesity [ 8 , 10 , 11 , 12 , 13 , 14 ]. Furthermore, maternal DII ® associations with offspring childhood respiratory issues, emotional and behaviour symptoms, and body mass index (BMI) trajectories from birth to adolescence have been reported [ 15 , 16 , 17 , 18 , 19 , 20 ]. Evidence suggests higher BMI is associated with DII ® in adults and children [ 1 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a variety of pregnancy cohorts, the DII ® or E-DII TM has been associated with outcomes such as maternal inflammation, gestational diabetes mellitus (GDM), preterm birth, birthweight, and neonatal adiposity, particularly in women with overweight and obesity [ 8 , 10 , 11 , 12 , 13 , 14 ]. Furthermore, maternal DII ® associations with offspring childhood respiratory issues, emotional and behaviour symptoms, and body mass index (BMI) trajectories from birth to adolescence have been reported [ 15 , 16 , 17 , 18 , 19 , 20 ]. Evidence suggests higher BMI is associated with DII ® in adults and children [ 1 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research to date regarding early life nutritional programming has focused on the mother but emerging evidence suggests that paternal nutritional status may also have an effect on child development, independently of maternal diet [ 24 , 104 ]. In a study conducted in Ireland, higher paternal E-DII scores, indicating a more pro-inflammatory diet, were associated with increased risk of childhood OWOB at 5 years [ 24 ], whereas higher paternal HEI scores, indicating higher dietary quality, were associated with reduced risk of childhood obesity [ 104 ]. Other studies reported that higher paternal BMI at conception was associated with increased offspring BMI [ 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall dietary quality may be more translatable to public health guidelines. Therefore, a variety of dietary scores and indices have been developed for nutritional epidemiology to assess dietary risk factors for non-communicable diseases [ 24 , 25 , 26 , 27 ]. These algorithms aim to evaluate the overall diet and categorise individuals according to the extent to which an individual’s eating behaviour is “healthy” based on primary nutritional data collected from 24-h quantitative dietary intake recalls, dietary records and food frequency questionnaires (FFQs) [ 28 ].…”
Section: Maternal Diet and Indices Of Dietary Quality And Dietary Inflammationmentioning
confidence: 99%
See 2 more Smart Citations